Employee engagement and supportive work environment in the relationship between HRM practices, work-life balance and doctors’ retention - Ahmed, Zeeshan (2021)
Employee retention continues to gain considerable attention among organizational psychologists and human resource management (HRM) experts. Globally, organizations are facing the issue of employee retention whereby a dearth of research exists on how it could be addressed, particularly in the services sector, with a special focus on the healthcare sector. Using the social exchange theory (SET), this study developed a theoretical framework based on the employee-organization relationship, which suggests that interactions between two parties must involve reciprocal interdependence. This study, therefore, investigated how HRM practices (such as recruitment and selection, compensation, training and development, and career advancement opportunities) and work-life balance influence employee engagement and doctors’ retention relationships. This study also investigated how employee engagement influences doctors’ retention. This study empirically tested the mediating influence of employee engagement on HRM practices, work-life balance, and doctors’ retention relationships and the moderating influence of a supportive work environment on employee engagement and doctors’ retention relationship. The data were collected through a survey of 385 public healthcare sector doctors working in Punjab, Pakistan. SPSS 23.0 and Smart-PLS 3.0 were used to analyze the data. The PLS path modeling results revealed significant direct relationships between compensation, work-life balance, and doctors’ retention. Additionally, the PLS path modeling results also demonstrated significant direct relationships between HRM practices, work-life balance, and employee engagement and a significant direct relationship between employee engagement and doctors’ retention. Moreover, the PLS path modelling results also revealed significant mediation of employee engagement between recruitment and selection, compensation, training and development, work-life balance, and doctors’ retention relationships, and moderation of a supportive work environment between employee engagement and doctors’ retention relationship. Based on the findings, the study proposed theoretical and practical implications, as well as limitations and future research directions.